A study of professional nurses’ perceptions of factors affecting the process of client education - Z Goudarzi; Kh Khosravi; N Bahrani; Kh Vaskooii; P Valipourgavgany; S Ghoghaei; M.S Mosaviniasigari; M Khayatali; H Zahedi; A Basiri (حیات, 2005)
Introduction: Education of patients and helping them to be independent in process of self-care in both health and disease is one of the basic responsibilities of nurses. Methods and Materials: This descriptive-analytic research was done to study perceptions of 317 nurses working in hospitals of Tehran University of Medical Sciences of factors affecting the process of patient education. Data was gathered by means of a questionnaire containing 30 questions about facilitating factors and 17 about inhibiting factors. We used Likert score to measure questions. Data analysis performed by SPSS software. Statistical test were Chi square, t test, variance analysis and correlation of variance. Results: The highest percentage of nurses (52.1%) believed that enough attention is not being paid to facilitating factors such as considering patient education as priority in patient care, nurses being responsible for patient education, considering patient education as a criteria in nurses annual evaluation, importance of patient education for nurse administrators, having in-service education about patient teaching and having proper time, place and personnel for patient education. Majority of nurses (57.4%) believed factors such as shortage of nurses, lack of proper place, time and patient motivation for receiving education, nurses and nurse administrators’ inattention to patient education and negative attitude of doctors toward patient education by nurses are inhibiting factors in process of education. Statistical tests showed a meaningful relation between demographic variables such as sex, clinical background, shift work and position and facilitating factors. There was also a meaningful relation between variables like working in more than one shift, having clinical experience of patient education and being evaluated for patient education during study of nursing and inhibiting factors.      Conclusion: This study shows low level of facilitating factors for patient education in hospitals of Tehran University of Medical Science. To improve patient education in these hospitals it is necessary to improve facilitating factors.